Stem cells (neoblasts) and positional information jointly dominate regeneration in planarians - Xuhui Chen (Heliyon)
Regeneration is the ability to accurately regrow missing body parts. The unparalleled regenerative capacity and incredible tissue plasticity of planarians, both resulting from the presence of abundant adult stem cells referred to as neoblasts, offer a unique opportunity to investigate the cellular and molecular principles underlying regeneration. Neoblasts are capable of self-renewal and differentiation into the desired cell types for correct replacement of lost parts after tissue damage. Positional information in muscle cells governs the polarity and patterning of the body plan during homeostasis and regeneration. For planarians, removal of neoblasts disables the regenerative feats and disruption of positional information results in the regeneration of inappropriate missing body regions, only the combination of neoblasts and positional information enables regeneration. Here, I summarize the current state of the field in neoblast lineage potential, subclasses and specification, and in the roles of positional information for proper tissue turnover and regeneration in planarians.